Financial Management Practices and Financial Sustainability of Non-Government Organisations in Uganda: A Case of Faraja Africa Foundation - Elsa Basemera (Uganda Christian University, 2023)
Non-Governmental Organizations being so crucial in developing countries for instance Uganda, their financial sustainability is a challenge since most of them rely on donor funding and the donors expectations need to be met. The purpose of the study was to determine the effect of financial management practices on financial sustainability of Non-Governmental Organizations in Uganda. The study mainly examined the effects of financial management practices on financial sustainability of Non-Governmental Organizations. The theory of budgeting, contingency management theory and sustainability theory were used to underpin this study. The study used a cross-sectional study design. The target population was forty-three comprising of senior account managers, Program managers, finance managers and administrators. Questionnaires were used as the main data collection instrument which the study relied on to collect data and was later analyzed by use of descriptive statistics in form of frequencies, mean, standard deviation and analysis such as Pearson correlation and regression analysis. The findings revealed that the financial management practices which were financial reporting, budgeting control and internal controls have a positive effect on the financial sustainability of NGOs. The study recommends that NGOs should emphasize and monitor financial management practices such as financial reporting, budgeting control and internal controls due to their significant influence on the financial sustainability of NGOs.
This is a dissertation.